Water Transport - The Challenge for the Automotive Industry in Slovakia - Kalina, Tomas; Jurkovic, Martin; Binova, Helena; Gardlo, Bruno (Communications - Scientific Letters of the University of Zilina, 2016)
An important factor in choosing the transport mode in the automotive industry is not only the current price but also the shipping time. In some cases the latter one is even crucial and significantly affects the choice of the transport mode. Geographical location of the port of Bratislava allows its direct connection to the North and Black Sea. The study provides a comparison of transportation time from the selected Slovak car producers and shows advantages of water transport. Time of delivery is a criterion that can be easily quantified and mutually compared. The fastest transportation mode - the road transport saves the time of delivery eight times more on average than the water transport in the European transport network. The waterway, on the other hand, is cheaper and environmentally friendlier.
Keywords: automotive industry; transportation time; vehicles; logistics operator; water transport